1998
DOI: 10.1074/jbc.273.30.18720
|View full text |Cite
|
Sign up to set email alerts
|

Direct Contact between T Lymphocytes and Human Dermal Fibroblasts or Synoviocytes Down-regulates Types I and III Collagen Production via Cell-associated Cytokines

Abstract: In many inflammatory diseases where tissue remodeling occurs, T cells are in close contact with mesenchymal cells. We investigated the effect of direct cell-cell contact between peripheral blood T lymphocytes or HUT-78 lymphoma cells and dermal fibroblasts or synoviocytes on the deposition of the major extracellular matrix components: types I and III collagen. Incubation of dermal fibroblasts and synoviocytes with plasma membrane preparations from resting T cells slightly increased the production of collagen I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 49 publications
2
48
0
Order By: Relevance
“…[44][45][46] The next set of experiments was aimed at verifying whether long-lived neutrophils have the potential to interact with primary human fibroblasts. Neutrophils prelabeled with calcein-AM were incubated with confluent synovial fibroblasts and adherent neutrophils were observed by fluorescent microscopy.…”
Section: Adhesion To Primary Human Fibroblastsmentioning
confidence: 99%
“…[44][45][46] The next set of experiments was aimed at verifying whether long-lived neutrophils have the potential to interact with primary human fibroblasts. Neutrophils prelabeled with calcein-AM were incubated with confluent synovial fibroblasts and adherent neutrophils were observed by fluorescent microscopy.…”
Section: Adhesion To Primary Human Fibroblastsmentioning
confidence: 99%
“…Previous studies have also documented specific interactions between T cells and synovial fibroblasts that result in cell:cell adhesion (7)(8)(9). It has been shown that freshly activated T cells can trigger functionally relevant responses by synovial fibroblasts, in part mediated by the effects of membrane-bound cytokines such as TNF-␣ that can be produced by activated T cells (10,11). However, most T lymphocytes in RA synovium lack the morphology, surface phenotype, and cytokine secretion profile of T cell blasts (1).…”
mentioning
confidence: 99%
“…According to this perspective, Th2 cells may act by releasing profibrotic cytokines (IL-4, IL-13) (18)(19)(20) that induce fibroblasts to produce extracellular matrix components, and Th1 cells by releasing antifibrotic cytokines (interferon-␥ [IFN␥]) that inhibit extracellular matrix production (21). In addition, T lymphocytes may act directly on fibroblasts by cell-cell contact (21)(22)(23), and their effect may be mediated by other cells such as macrophages (24).…”
mentioning
confidence: 99%